Effects of Marital Status and Social Support on Antenatal Depression: A Meta-Analysis - Meita Tyas Nugrahaeni; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2023)
Background: Pregnancy is a period of increased vulnerability to depression incidence, especially if the pregnancy is accompanied by additional demands. Antenatal depression is depression that occurs during pregnancy characterized by certain symptoms, namely anxiety, distress, confusion, and excessive fear. The study aims to estimate the effect size of marital status and social support on the incidence of antenatal depression in pregnant women. Subjects and Method: The study used systematic review and meta-analysis with PICO, Population: pregnant women; Intervention: marital status and strong social support; Comparison: unmarried marital status and weak social support. Outcome: antenatal depression. The articles used were obtained from several databases namely Google Scholar, Pubmed, SpringerLink, and Science Direct. The article search keywords were "Antenatal Depression" AND "Marital Status" AND "Social Support" AND "Pregnant Women". The inclusion criteria for the articles were full-text articles in English using cross-sectional observational study design, published between 2012 and 2022, the study subject was pregnant women, and the size of the association was presented in adjusted Odds ratio (aOR). The data were analyzed using Review Manager app (RevMan 5.3). Results: A total of 17 cross-sectional articles originated from Asia and Africa including Qatar, Thailand, China, Ethiopia, Tanzania, Nigeria, and Rwanda for systematic review and meta-analysis with a total population of 8,723 pregnant women. Pregnant women with unmarried marital status could contribute to the worsening condition of pregnant women that generated antenatal depression (aOR= 2.76; 95% CI= 1.75 to 4.36; p< 0.0001).  Meanwhile, pregnant women with weak social support could contribute to the worsening of the condition of pregnant women that generated antenatal depression (aOR= 2.22; 95% CI= 1.42 to 3.46; p= 0.005). Conclusion: Marital status and social support can improve the prevention of antenatal depression in pregnant women. Keywords: marital status, social support, pregnant women, antenatal depression. Correspondence: Meita Tyas Nugrahaeni. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: meitatyas04@gmail.com. Mobile: +6285974825459.